Strategies to develop classroom management in the learning teaching process, in the first year of basic education - Santillán Duchi, Roxanna Estefanía (Machala : Universidad Técnica de Machala, 2016)
Executive summary strategies to develop classroom management in the learning-teaching process, in first year of basic education. author: santillan duchi roxanna estefania. the main theoretical dimension of practical research is to be solved by the research of strategies to develop efficient classroom management in which teachers and students learn and create a supportive environment without misbehavior among them. the resources used to solve this research are the following: strategies to teach english, common classroom management, learning process, teaching process, teaching environments. a typical english class in the first year of basic education in 9 octubre high school, shows that many students have misbehavior during a lesson and the teachers do not know basic rules to motivate the class and also neither apply any classroom management strategy to solve the problem. it is important to mention some questions which will serve to solve this study case, what does classroom management means in teaching english? what is a classroom management interaction? how to give instructions? what are models and approaches of classroom? what is a classroom management skill? what are the most common approaches used in classroom management? why is important the teacher’s role in classroom management in teaching english? in addition, the current research will apply the inductive method, it will allow to make conclusions and it will explain all about general to the particular information, and the main goal of this research is the experience as an english teacher.
Keywords: CLASSROOM MANAGEMENT; SKILL; APPROACH; TECHNIQUE; STUDENT; STRATEGY